2004
DOI: 10.1111/j.1365-2621.2004.tb17882.x
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐beam Irradiation Preserves the Quality of White Button Mushroom (Agaricus bisporus) Slices

Abstract: The effect of electron-beam irradiation on microbial counts, color, texture, and enzyme activity of mushroom slices was evaluated at dose levels of 0.5, 1, 3.1, and 5.2-kGy. Irradiation levels above 0.5 kGy reduced total plate counts, yeast and mold, and psychrotrophic counts to below detectable levels and prevented microbial-induced browning. Firmness of all samples was similar during storage except for the 5.2-kGy sample. Color was preserved by irradiation as evidenced by the higher L* values. Electron-beam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…Little information is available on spoilage of mushrooms caused by yeasts. Koorapati et al (2004) and Chikthimmah (2006) reported on the control of microbial spoilage after product irradiation. In their experiment, irradiation reduced all microbial counts including bacteria, yeasts and moulds, and prolonged mushroom shelf life.…”
Section: Discussionmentioning
confidence: 99%
“…Little information is available on spoilage of mushrooms caused by yeasts. Koorapati et al (2004) and Chikthimmah (2006) reported on the control of microbial spoilage after product irradiation. In their experiment, irradiation reduced all microbial counts including bacteria, yeasts and moulds, and prolonged mushroom shelf life.…”
Section: Discussionmentioning
confidence: 99%
“…All EB doses used in the present study reduced the YMC to below reference criteria for dried fruits which have maximum value of 3 log CFU/g (Food Administration, 1995). Another study by Koorapati, Foley, Pilling, and Prakash (2004) found EB treatment in the range from 0.5 kGy to 5.2 kGy reduced TVC, YMC, and psychrotrophic counts to below detectable levels and prevented microbial-induced browning in mushroom.…”
Section: Microbial Loadmentioning
confidence: 97%
“…Microbial degradation resulting in changes such as browning and softening was clearly delayed in irradiated samples (Koorapati et al 2004). From the above two experiments we can suggest that irradiation was effective in reducing the microbial count.…”
Section: Microbiological Quality Of Irradiated Grape Pomacementioning
confidence: 99%